Chronobiology Meets Quantum Biology: A New Paradigm Overlooking the Horizon? - Mazzoccoli, Gianluigi (Frontiers in Physiology, 2022)
Biological processes and physiological functions in living beings are featured by oscillations with a period of about 24 hours (circadian) or cycle at the second and third harmonic (ultradian) of the basic frequency, driven by the biological clock. This molecular mechanism, common to all kingdoms of life, comprising animals, plants, fungi, bacteria, and protists, represents an undoubted adaptive advantage allowing anticipation of predictable changes in the environmental niche or of the interior milieu. Biological rhythms are the field of study of Chronobiology. In the last decade, growing evidence hints that molecular platforms holding up non-trivial quantum phenomena, including entanglement, coherence, superposition and tunnelling, bona fide evolved in biosystems. Quantum effects have been mainly implicated in processes related to electromagnetic radiation in the spectrum of visible light and ultraviolet rays, such as photosynthesis, photoreception, magnetoreception, DNA mutation, and not light-related such as mitochondrial respiration and enzymatic activity. Quantum effects in biological systems are the field of study of Quantum biology. Rhythmic changes at the level of gene expression as well as protein quantity and subcellular distribution confer temporal features to the molecular platform hosting electrochemical processes and non-trivial quantum phenomena. Precisely, a huge amount of molecules plying scaffold to quantum effects show rhythmic level fluctuations and this biophysical model implies that timescales of biomolecular dynamics could impinge on quantum mechanics biofunctional role. The study of quantum phenomena in biological cycles proposes a profitable “entanglement” between the areas of interest of these seemingly distant scientific disciplines to enlight functional roles for quantum effects in rhythmic biosystems.